Perubahan-Perubahan Paradigma Dan Praksis Misi Gereja Di Era Society 5.0 - Adrianus Pasasa; Yossua Hartaya (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2021)
Facing the massive changes that occur in society as a result of the Industrial Revolution 4.0 era, an era marked by a blend of technology that blurs the lines between the physical, digital, and biological fields. Between the physical and digital become connected. Acceleration towards the digital world was stimulated by the emergence of the Covid-19 pandemic. The digital world becomes a world no longer a virtual world but a real world whose existence is in our midst. Changes in the Industrial Revolution 4.0 era will greatly impact the religious social life of mankind. The development of the Industrial Revolution 4.0 era, has given birth to changes in community culture which of course must also change the paradigm and praxis of the church's mission. The paradigm and praxis of the church's mission need to be evaluated and rethinking and reconstruction need to be carried out in the light of God's Word and contextually. This study uses the following methods: 1. Systematic Literature Review by collecting several references through literature study so as to obtain data related to the paradigm and praxis of the church's mission that is developing; 2. Hermeneutics by examining several Bible verses related to the topic as the basis for the construction of paradigms and missionary praxis in the era of the Industrial Revolution 4.0. The results of this research are expected to be able to contribute to the church, especially with regard to the construction of the paradigm and practice of the church in carrying out its mission in the era of the Industrial Revolution 4.0. The church can take advantage of the opportunities resulting from the Industrial Revolution 4.0 era. in carrying out its mission.